NEGOTIATIONS BETWEEN RELIGION AND CULTURE IN CONTEMPORARY MINANGKABAU SOCIETY - Vivi Yulia Nora; Novi Hendri; Hardi Putra Wirman (Program Studi Sosiologi Universitas Malikussaleh, 2026)
This article examines the dynamic negotiation between Islam and Minangkabau adat in contemporary West Sumatra, framed within the philosophical principle of Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS–SBK). While previous studies often emphasize harmony between adat and Islam, this research argues that their relationship is better understood as an ongoing process of negotiation shaped by legal pluralism, cultural hybridity, and public reasoning. Drawing on qualitative methods—literature review, limited ethnographic observation, and in-depth interviews—this study employs the theoretical frameworks of cultural hybridity (Bhabha), legal pluralism (Benda-Beckmann), and Islamic public reasoning (Bowen). The findings reveal that the interaction between adat and Islam is not static but continuously reconstructed through social practices such as inheritance, marriage, gender relations, and local governance. This study highlights the urgency of understanding how local Islamic practices adapt to modernity, globalization, and changing gender norms. It contributes to sociological debates by demonstrating that Islam in Minangkabau operates as a flexible and dialogical system that accommodates local traditions without erasing them.